Cómo se construye al enemigo - Gavilán Sánchez, Lurgio (2023)
From an auto-ethnographic perspective, the study analyzes the construction of different types of enemies in the context of the internal armed conflict and state of exception that took place in Ayacucho, Peru, between1980 and 2000. The result suggests a critical examination of the states of exception. Well then, beyond the reduction to a single enemy-friend (Sendero Luminoso and the Peruvian State), new qualitative views showa complex kaleidoscopic situation of multiple faces of the social subject, which involves examining the network of adversaries: troops, terrucos, cachacos, even a statue of the Inca. Thus, in the face of dichotomous and stigmatizing visions, knowing these dissimilar enemies allows us to betterunderstand the victim and perpetrator produced in a context of violence, with their own interests and local cultural logics, since these adversaries caused polarization and fractures of the social fabric.